Physical Properties and Consumer Acceptance of White Bread with The Substitution of Coconut Dregs and Avocado Seed Flour - Winda Dwi Oktarini; Delsi Anjarwati; Ari Setiawan; Nabilla Dhiya Ulhaq; Desiana Nuriza Putri (agriTECH, 2023)
Analysis of the relationship between physical properties and consumer acceptance, which is commonly influenced by sensory properties is crucial in delivering a high-quality food product. Therefore, this study aimed to analyze the effect of physical properties, including hardness, adhesiveness, dough expansion, specific volume, color intensity (L*, a*, b*, and °hue), browning index, and analysis of consumer acceptance by employing Partial Least Squares (PLS) regression. The analysis focused on high-fiber white bread made by substituting coconut dregs and avocado seed flour with different ratios, denoted as P0 (control), P1 (90% wheat flour: 5% coconut dregs flour: 5% avocado seed flour), P2 (85% wheat flour: 10% coconut dregs flour: 5% avocado seed flour), P3 (80% wheat flour: 15% coconut dregs flour: 5% avocado seed flour), P4 (75% wheat flour: 20% coconut dregs flour: 5% avocado seed flour), and P5 (70% wheat flour: 25% coconut dregs flour: 5% avocado seed flour). The results showed that consumer preferences had a positive correlation with the physical properties of white bread, including hardness, adhesiveness, dough expansion, specific volume, as well as colors L*, and °hue, while, a*, b*, and had a negative correlation with the browning index. The circular correlation analysis between physical properties and consumer acceptance indicated that the substitution of 25% coconut dregs flour and 5% avocado seed flour in white bread was accepted by consumers.